Factors Associated with Postpartum Iron Deficiency Anemia - Sabahat Fatima, Sameena, Tahmina Mahar, Mahjabeen, Shoaib-Un-Nisa Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To study the factors associated with postpartum iron deficiency anemia. Study Design: Case-control study. Place and Duration of Study: Department of Obstetrics & Gynecology Unit-II, Ghulam Muhammad Mahar Medical College Sukkur, Pakistan from 1st January 2020 to 31st December 2020 Methodology: Five hundred and seventy six women were included in which 144 women with postpartum iron deficiency anemia (Hb <11 g/dl at 24 to 48 hours post-delivery) were as case group and 432 women without postpartum iron deficiency anemia (Hb >11gdl at 24-48 hours post delivery) were as control group. Results: There was not significant (p=0.87) difference between case and control groups. Multiparity was associated with post-partum iron deficiency anemia (p=0.012). Postpartum iron deficiency anemia was about two times more likely in multiparous (OR=1.65; 95%CI: 1.12 to 2.44) than primiparious, failure to exclusively breast-feeding was also associated (p=0.003), postpartum iron deficiency anemia was two times more likely in those women those were not exclusive breast-feeding (OR=1.95; 95%CI: 1.24 to 3.07) than those were. Similarly post-partum iron deficiency anemia was ten times more likely in those women whose education was below or metric (OR=10.54; 95%CI: 2.85 to 39.03) than those who are highly educated. On the other hand, obesity was not associated (p=0.075) unadjusted odd ratio of obese was 0.68 (95%CI: 0.44 to 1.04) Conclusion: Multiparity failure to exclusively breast feed is significantly associated with postpartum iron deficiency anemia. Keywords: Postpartum iron deficiency anemia, obesity, multiparty